But is My Resource Included? How to Manage, Develop, and Think about the Content in Your Discovery Tool. Issue 1 (18th May 2016) - Moore, Monica
Abstract : Implementing discovery tools and getting them to work with existing library services often leaves very little time for their promotion and for the thoughtful, ongoing evaluation and curation of their content. However, the expectations and experiences that users have about discovery tools are often directly related to the content and the way that content is described. In our efforts to work with vendors to resolve the underlying business issues that prevent us from having all of the metadata for our resources included in our discovery tools, we may have lost sight of our role in curating and evaluating the usefulness of the content that is already included in them.